2022
DOI: 10.2337/dc21-1526
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Stress Hyperglycemia Ratio on Short-term and Long-term Poor Prognosis in Patients With Acute Coronary Syndrome: Insight From a Large Cohort Study in Asia

Abstract: OBJECTIVE In recent years, some studies have indicated that a novel marker described as the stress hyperglycemia ratio (SHR) can reflect true acute hyperglycemic status and is associated with the short-term poor prognosis in patients with acute myocardial infarction. In the current study we evaluated the association of SHR with adverse cardiovascular events among patients with acute coronary syndrome (ACS). RESEARCH DESIGN AND METHODS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 41 publications
(30 reference statements)
5
70
0
Order By: Relevance
“…Our study also exhibits U-shaped associations of SHR with in-hospital adverse events in people with type 2 diabetes hospitalized with heart failure, suggesting the nadir range of SHR at 0.79 to 1.08. This is consistent with a recent study that SHR is nonlinearly associated with in-hospital cardiac death and MI in patients with ACS and the inflection point is at SHR of 0.78 [ 9 ]. A prior study in Spain [ 8 ] found the third tertile of SHR with a mean of around 1.2 was associated with the lowest 4 year mortality in people with diabetes hospitalized for acute heart failure, which was in line with our findings to some extent.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study also exhibits U-shaped associations of SHR with in-hospital adverse events in people with type 2 diabetes hospitalized with heart failure, suggesting the nadir range of SHR at 0.79 to 1.08. This is consistent with a recent study that SHR is nonlinearly associated with in-hospital cardiac death and MI in patients with ACS and the inflection point is at SHR of 0.78 [ 9 ]. A prior study in Spain [ 8 ] found the third tertile of SHR with a mean of around 1.2 was associated with the lowest 4 year mortality in people with diabetes hospitalized for acute heart failure, which was in line with our findings to some extent.…”
Section: Discussionsupporting
confidence: 93%
“…Analysis may be necessary. Finally, like many other studies investigating stressful hyperglycemia [ 4 , 7 , 9 ], since many participants were admitted to the hospital from the emergency room, this study was unable to measure the impact of diet on glucose. It calls for prospective studies to collect information regarding diet intake, intravenous glucose infusion and blood glucose measure.…”
Section: Discussionmentioning
confidence: 98%
“…In an animal model of shock, external highly permeable glucose increased cardiac output and improved survival [ 17 ]. However, several studies have reported that stress hyperglycemia is strongly associated with adverse clinical outcomes among patients with critical illnesses, including myocardial infarction, stroke, sepsis, and COVID-19 [ 11 , 18 , 19 ]. Stress hyperglycemia has been identified as an independent risk factor for worsened prognoses in patients with ACS [ 4 6 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al reported that SHR was significantly associated with 30-day mortality in patients with STEMI and that the predictive efficiency of the TIMI risk score can be improved after adding SHR as one point [ 12 ]. Yang et al observed a J-shaped relationship between SHR and in-hospital cardiac death in patients with ACS who underwent the implantation of a drug-eluting stent [ 11 ]. Chen et al reported a dose-response relationship between SHR and in-hospital deaths in patients > 75 years of age with acute myocardial infarction [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation